Monoclonal antibodies to induce therapeutic immunological tolerance - Waldmann, Herman (Henry Stewart Talks, 2019)
Short-term treatment for a long-term benefit, Antibodies and induction of therapeutic tolerance, Coreceptor and costimulation blockade during antigen recognition, Regulatory T-cells in transplantation tolerance, Transplant models and transgenic mice, Immunologically privileged microenvironments